Litigating the Limits of Religion: Minority and Majority Concerns about Institutional Religious Liberty in India - Bauman, Chad M. (Religions, 2021)
Western religious liberty advocates tend to focus on restrictions placed on minority religious communities, particularly when advocating abroad, that is, outside of the country in which they reside. In all contemporary democracies, however, adherents of religious majorities also express concerns about religious liberty. For this reason, the article considers both minority and majority concerns about institutional religious freedom in India. This essay provides an overview of religious freedom issues, with a particular focus on institutions, though, as I acknowledge, it is not always simple to distinguish individual from institutional matters of religious freedom. After describing various minority and majority concerns about institutional religious freedom in India, and demonstrating that many of them are related to the Indian government’s distinctive approach to managing religion and religious institutions, I make the argument that while some cross-cutting issues provide the possibility of interreligious understanding and solidarity in matters of religious liberty advocacy, such solidarity will not emerge without considerable effort because of the fact that debates about religious liberty in India often fundamentally involve debates about the very nature of religion itself, and these debates tend to divide rather than unite India’s majority and minority religious communities.